2020
DOI: 10.3389/fmicb.2020.558747
|View full text |Cite
|
Sign up to set email alerts
|

Active Transposition of Insertion Sequences by Oxidative Stress in Deinococcus geothermalis

Abstract: Radiation-resistant bacterium Deinococcus geothermalis has a total of 73 insertion sequences (ISs) in genomes, and some of them are actively transposed to other loci with replicative mode due to oxidative stress of hydrogen peroxide treatment. Here, we detected two transposition events in wild-type (WT) strain and LysR family member gene disrupted strain (dgeo_2840). Similar to our previous report (Lee et al., 2019), phytoene desaturase (dgeo_0524), a key enzyme of carotenoid biosynthesis, was disrupted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 57 publications
0
30
0
2
Order By: Relevance
“…Finally, it is important to mention that induced mutagenesis via transposition of insertion sequence (IS) elements has also been described in two Deinococcus species. In D. radiodurans and D. geothermalis, which lack TLS polymerases, transposition of certain IS elements is induced after exposure to radiation or oxidative stress [65][66][67]. Other Deinococcus species, including D. deserti [4], also contain IS elements, but it is currently unknown if transposition of one or more of these ISs is stimulated after stress exposure.…”
Section: Presence Of Imuy-imub-c-dnae2 Mutagenesis Cassette In Many Dmentioning
confidence: 99%
“…Finally, it is important to mention that induced mutagenesis via transposition of insertion sequence (IS) elements has also been described in two Deinococcus species. In D. radiodurans and D. geothermalis, which lack TLS polymerases, transposition of certain IS elements is induced after exposure to radiation or oxidative stress [65][66][67]. Other Deinococcus species, including D. deserti [4], also contain IS elements, but it is currently unknown if transposition of one or more of these ISs is stimulated after stress exposure.…”
Section: Presence Of Imuy-imub-c-dnae2 Mutagenesis Cassette In Many Dmentioning
confidence: 99%
“…Our previous studies have found that multi-copy IS elements, IS Dge5 , IS Dge6 , IS Dge7 , and IS Dge11 members, used a replicative transposition action mode and their movement was actively triggered by oxidative stress resulting in enhancing the copy number through active transposition. 17 , 18 There are 6 single IS members (IS Dge1 , IS Dge8 , IS Dge10 , IS Dge14 , IS Dge15 , and IS Dge17 ). Interestingly, all 7 IS copies of IS Dge13 type are found in plasmid pDGEO02.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of the LysR family regulator gene Dgeo_2840 resulted in the transposition of IS Dge6 type IS into carotenoid biosynthesis enzymes through replicative transposition in an oxidative-stress induced manner. 18 Although the genome of a strain of wild-type D. geothermalis already contains 10 copies of IS Dge5 , 5 copies of IS Dge6 , and 4 copies of IS Dge7 , active transposition of their ISs was caused by oxidative stress. In other words, hydrogen peroxide treatment under conditions without specific DNA-binding proteins, Dgeo_0257 and Dgeo_2840, resulted in further gene disruption caused by active transposition of distinct IS element ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress-induced transposition has been reported for several organisms by respective stressors ( Zhang and Saier, 2016 ; Vandecraen et al, 2018 ; Lee et al, 2019 , 2020 ). In G. stearothermophilus CU21, IS 4 and IS 21 members have been reported to achieve transposition during growth inhibition by chloramphenicol exposure ( Xu et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%